Antitumorigenic Effects of Inhibiting Ephrin Receptor Kinase Signaling by GLPG1790 against Colorectal Cancer Cell Lines In Vitro and In Vivo. (27th February 2020) - Colapietro, Alessandro; Gravina, Giovanni Luca; Petragnano, Francesco; Fasciani, Irene; Scicchitano, Bianca Maria; Beirinckx, Filip; Pujuguet, Philippe; Saniere, Laurent; Van der Aar, Ellen; Musio, Daniela; De Felice, Francesca; Mattei, Vincenzo; et al.
Abstract : Erythropoietin-producing hepatocellular receptors (Eph) promote the onset and sustain the progression of cancers such as colorectal cancer (CRC), in which the A2 subtype of Eph receptor expression has been shown to correlate with a poor prognosis and has been identified as a promising therapeutic target. Herein, we investigated, in vitro and in vivo, the effects of treatment with GLPG1790, a potent pan-Eph inhibitor. The small molecule has selective activity against the EphA2 isoform in human HCT116 and HCT15 CRC cell lines expressing a constitutively active form of RAS concurrently with a wild-type or mutant form of p53, respectively. GLPG1790 reduced EPHA2 phosphorylation/activation and induced G1 /S cell-cycle growth arrest by downregulating the expression of cyclin E and PCNA, while upregulating p21 Waf1/Cip1 and p27 Cip/Kip . The inhibition of ephrin signaling induced quiescence in HCT15 and senescence in HCT116 cells. While investigating the role of CRC-related, pro-oncogenic p53 and RAS pathways, we found that GLPG1790 upregulated p53 expression and that silencing p53 or inhibiting RAS (human rat sarcoma)/ERKs (extracellular signal-regulated kinase) signaling restrained the ability of GLPG1790 to induce senescence in HCT116 cells. On the other hand, HCT15 silencing of p53 predisposed cells to GLPG1790-induced senescence, whilst no effects of ERK inhibition were observed. Finally, GLPG1790 hindered the epithelial-mesenchymal transition, reduced the migratory capacities of CRC, and affected tumor formation in xenograft models in vivo more efficiently using HCT116 than HCT15 for xenografts. Taken together, our data suggest the therapeutic potential of GLPG1790 as a signal transduction-based therapeutic strategy in to treat CRC.